Upaya Pemberdayaan Ekonomi Umat Melalui Program Pendampingan UMKM Oleh Lazismu Kota Depok - Atmawidjaja, Rd. Heri Solehudin; Gunawan, Rudy; Ghulam D., Rifma; Munawwaroh, Saadiatul; Darwis, Syahrudin; Sylvester, Pisonia (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Economic empowerment of the people is a critical aspect in efforts to improve community welfare. One of the methods used to achieve this goal is through the Micro, Small and Medium Enterprises (MSME) assistance program carried out by Lazismu Depok City. This research aims to evaluate the impact and effectiveness of the community economic empowerment program implemented by Lazismu Depok City. Method: The research methodology involves analysis of primary and secondary data, including interviews with MSME owners who have participated in the Lazismu mentoring program. Results: The research results show that this program has made a positive contribution to the development and sustainability of the MSMEs involved. Apart from that, this research also explores the challenges and obstacles faced by MSMEs during the empowerment process. Conclusion: The results of this research can provide guidance for Lazismu Depok City in increasing the effectiveness and relevance of the community's economic empowerment program, as well as making a positive contribution to the economic development of the community as a whole.